2017
DOI: 10.1007/s10461-017-1755-0
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Psychosocial Interventions to Reduce Drug and Sexual Blood Borne Virus Risk Behaviours Among People Who Inject Drugs

Abstract: Opiate substitution treatment and needle exchanges have reduced blood borne virus (BBV) transmission among people who inject drugs (PWID). Psychosocial interventions could further prevent BBV. A systematic review and meta-analysis examined whether psychosocial interventions (e.g. CBT, skills training) compared to control interventions reduced BBV risk behaviours among PWID. 32 and 24 randomized control trials (2000-May 2015 in MEDLINE, PsycINFO, CINAHL, Cochrane Collaboration and Clinical trials, with an updat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 60 publications
(344 reference statements)
1
11
1
2
Order By: Relevance
“…Second, we did not include measures of sexual and drug-use risk behaviors and thus were unable to directly examine the extent to which this educational intervention influenced frequency of HIV + HCV-related risk behaviors. However, prior studies have reported a strong concordance between HIV and HCV education and reductions in high-risk behaviors, as well as increases in protective health behaviors (Copenhaver et al, 2006; Gilchrist et al, 2017; Meader et al, 2010; Shah and Abu-Amara, 2013). Finally, we did not include HIV or HCV screening and thus cannot evaluate whether infectious disease status changed as a function of the educational intervention.…”
Section: Discussionmentioning
confidence: 94%
“…Second, we did not include measures of sexual and drug-use risk behaviors and thus were unable to directly examine the extent to which this educational intervention influenced frequency of HIV + HCV-related risk behaviors. However, prior studies have reported a strong concordance between HIV and HCV education and reductions in high-risk behaviors, as well as increases in protective health behaviors (Copenhaver et al, 2006; Gilchrist et al, 2017; Meader et al, 2010; Shah and Abu-Amara, 2013). Finally, we did not include HIV or HCV screening and thus cannot evaluate whether infectious disease status changed as a function of the educational intervention.…”
Section: Discussionmentioning
confidence: 94%
“…Research targeting MSM, PWID, and transgender populations is needed to understand the transmission risk factors and specific structural, social, behavioral, and epidemiological factors impacting these groups. While there is a considerable body of HIV prevention intervention research focusing on MSM and PWIDs in other parts of the world [63,64], none have been specific to the Philippines. It remains unclear whether existing prevention interventions are adaptable or require distinct design for this national context.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, mental health counseling plays an important role in HIV prevention. Psychotherapy, particularly behavioral interventions, similar to the effect of OST, has been shown to reduce HIV-acquisition risk in a number of studies on MSM25 and PWID 26,27. However, varying evidence exists on the efficacy of single vs multiple psychosocial interventions and educational interventions.…”
Section: Discussionmentioning
confidence: 99%